EFFECTIVENESS OF APPLICATION OF ECONOMICS FLIPBOOK E-MODULE LEARNING MEDIA WITH PROBLEM BASED LEARNING (PBL) LEARNING MODEL IN IMPROVING LEARNING OUTCOMES OF CLASS X STUDENTS OF SMAN 3 MOJOKERTO CITY: EFEKTIVITAS PENERAPAN MEDIA PEMBELAJARAN E-MODUL FLIPBOOK EKONOMI DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMAN 3 KOTA MOJOKERTO - Ainur Rochmawati; Dhiah Fitrayati; Titin Uswati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Based on initial observations, researchers found that the majority of students had difficulty learning Economics material because there was a lot of material to study, so they became passive in participating in learning activities. Many of them are less interested and are busy with other activities such as playing on their cellphones, feeling sleepy, or chatting alone with friends. This has an impact on student learning outcomes. To overcome this problem and create technology-based 21st century learning and increase students' understanding in aspects of knowledge, research was conducted with the aim of testing the effectiveness of implementing the economic flipbook e-module learning media using the PBL learning model in improving the learning outcomes of class X students at SMAN 3 Mojokerto City. The sample for this research consisted of students in classes X4 & X5, totaling 36 students. The research method used is a descriptive quantitative approach with experimental research using the One Group Pretest-Posttest Design model. This research model consists of two groups, namely the experimental group and the control group. Students from both groups were given pretest and post-test questions. The results of the N-Gain score test show that the average score of the control group did not show a significant increase and was less effective in improving student learning outcomes. The average N-Gain Score value in the control group was 0.41 or an N-Gain Score (%) of 41.09%, so it was categorized as moderate and interpreted as less effective. Meanwhile, the experimental group showed different results. Their N-Gain Score value is 0.85 or N-Gain Core (%) of 85.42%, so the use of economic flipbook e-modules with the Problem Based Learning (PBL) learning model is categorized as high and interpreted as effective.